Business Capacity as a Strategic Mediator Between Digital Marketing and Sustainable Performance: Evidence from Indonesian - Septianing; Sri Wahyuni; Rif'ah; Slamet; Jati Nugroho (International journal of technology and education research, 2026)
Sustainable business performance remains a critical challenge for small and medium-sized enterprises (SMEs) operating in increasingly competitive and digital business environments. While previous studies have examined the direct effects of digital marketing and strategic management on organizational performance, limited attention has been given to the role of organizational capability as a strategic mechanism linking these factors to sustainability. Drawing upon the Knowledge-Based View (KBV), this study investigates the mediating role of Business Capacity in the relationships between Social Media Marketing, Strategic Orientation, Government Regulation, and Sustainable Performance among handicraft SMEs in Indonesia. Data were collected from 120 handicraft SMEs in Magelang Regency using purposive sampling and analyzed through Structural Equation Modeling (SEM) with AMOS 24. The results indicate that Social Media Marketing, Strategic Orientation, and Government Regulation significantly enhance Business Capacity. Furthermore, Business Capacity exerts the strongest positive influence on Sustainable Performance, confirming its role as a strategic organizational capability that transforms external knowledge and managerial resources into sustainable business outcomes. This study extends the Knowledge-Based View by demonstrating that organizational knowledge embedded in financial capability, customer management, internal business processes, and organizational learning is fundamental to achieving long-term sustainability. The findings provide practical implications for SME managers and policymakers in designing knowledge-driven capability development programs that strengthen sustainable competitiveness.